On the genetics of retinitis pigmentosa and on mutation-independent approaches to therapeutic intervention - Humphries, Peter; Farrar, Gwyneth (My University, 2002)
Retinitis pigmentosa (RP), the group of hereditary conditions involving death of retinal photoreceptors, represents the most prevalent cause of visual handicap among working populations in developed countries. Here we provide an overview of the molecular pathologies associated with such disorders, from which it becomes clearly apparent that RP is one of the most genetically heterogeneous of hereditary conditions for which molecular pathologies have so far been elucidated. While heterogeneity of such magnitude would appear to represent a major impediment to the development of therapeutics, mutation-independent approaches to therapy are being developed to effectively by-pass such diversity in genetic aetiology. The implications of such technologies in terms of therapeutic intervention in RP, and indeed other genetically heterogeneous conditions, will be addressed.
PUBLISHED
Keywords: Molecular biology